Amyloid-beta oligomers induce Parkin-mediated mitophagy by reducing Miro1. Issue 23 (11th December 2020) - Kam, Min Kyoung; Lee, Dong Gil; Kim, Bokyung; Huh, Jae-Won; Lee, Hong Jun; Park, Young-Ho; Lee, Dong-Seok
Abstract : Alzheimer's disease (AD) is a neurodegenerative disease associated with the accumulation of amyloid-beta oligomers (AβO). Recent studies have demonstrated that mitochondria-specific autophagy (mitophagy) contributes to mitochondrial quality control by selectively eliminating the dysfunctional mitochondria. Mitochondria motility, which is regulated by Miro1, is also associated with neuronal cell functions. However, the role played by Miro1 in the mitophagy mechanism, especially relative to AβO and neurodegenerative disorders, remains unknown. In this study, AβO induced mitochondrial dysfunction, enhanced Parkin-mediated mitophagy, and reduced mitochondrial quantities in hippocampal neuronal cells (HT-22 cells). We demonstrated that AβO-induced mitochondrial fragmentation could be rescued to the elongated mitochondrial form and that mitophagy could be mitigated by the stable overexpression of Miro1 or by pretreatment with N-acetylcysteine (NAC)-a reactive oxygen species (ROS) scavenger-as assessed by immunocytochemistry. Moreover, using time-lapse imaging, under live cell-conditions, we verified that mitochondrial motility was rescued by the Miro1 overexpression. Finally, in hippocampus from amyloid precursor protein (APP)/presenilin 1 (PS1)/Tau triple-transgenic mice, we noted that the co-localization between mitochondria and LC3B puncta was increased. Taken together, these results indicated that up-regulated ROS, induced by AβO, increased the degree of mitophagy and decreased the Miro1 expression levels. In contrast, the Miro1 overexpression ameliorated AβO-mediated mitophagy and increased the mitochondrial motility. In AD model mice, AβO induced mitophagy in the hippocampus. Thus, our results would improve our understanding of the role of mitophagy in AD toward facilitating the development of novel therapeutic agents for the treatment of AβO-mediated diseases.